PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS NEGERI 11 SIJUNJUNG - hariman syaleh (Universitas Lancang Kuning, 2018)
ABSTRACT : This study aims to analyze the influence of work motivation and work discipline on the performance of teachers of State Senior High School 11 Sijunjung. Here the authors describe the effect of work motivation and work discipline on the performance of teachers in State Senior High School 11 Sijunjung. The number of population in this research is counted 24 people so that the entire population is made sample by using census method. Data were collected through questionnaire distribution with Likert scale model then tested to validity and reliability of the questionnaire. Data analysis technique used is multiple linear regression method using SPSS 20.00 program. The purpose of multiple linear regression to see the relevance of the influence of independent variables to the dependent variable. The result of this research is a). Motivation of work (X1) there is a positive and significant influence on the performance of teachers at State Senior High School 11 Sijunjung. b). Work discipline (X2) there is a positive and significant influence on the performance of teachers at State Senior High School 11 Sijunjung. c). Then Motivation work and Discipline work together - there is a positive and significant influence on the performance of teachers at State Senior High School 11 Sijunjung so that the hypothesis can be accepted. Keywords: Motivation; Discipline; Performance.